A management processes and activities in intensive knowledge: a study in the beverage industry - Rossés, Gustavo Fontinelli; Sccott, Carla Rosane da Costa; Godoy, Leoni Pentiado; Silva, Alexandre Fontinelli da; Viero, Claudinei (Revista de Administração da UFSM, 2017)
The growth of the beverage industry in Brazil, in the case of volumes produced and consumed, infers the constant pursuit of strategies, tools and innovative attitudes, in which the process management and knowledge management play a key role. Thus, the focus of this study is focused on analysis of knowledge-intensive activities in a given process in the organizations of the knowledge society, contextualized, through case study, in a beverage industry of the City of Santa Maria, in the State of Rio Grande do Sul. Descriptive and qualitative methods were needed to support the methodology, whose collection was done through interviews, document analysis and observation, so as to make possible the analysis of the data. That said, it was observed that the organization studied is knowledge intensive and recognizing process management as a tool for organizational management oriented optimization strategies and results. It is noteworthy, however, that it lacks proper structuring of these activities. Thus, after analysis it was possible contributing suggesting a new process more detailed and focused on knowledge-intensive activities considered.